Objectively-measured sedentary time, habitual physical activity and bone strength in adults aged 62 years: the Newcastle Thousand Families Study. (24th April 2019) - Hind, K; Hayes, L; Basterfield, L; Pearce, M S; Birrell, F
Abstract: Background: The influence of sedentary time and habitual physical activity on the bone health of middle aged adults is not well known. Methods: Bone mineral density (BMD) and hip bone geometry were evaluated in 214 men ( n = 92) and women ( n = 112) aged 62.1 ± 0.5 years from the Newcastle Thousand Families Study birth cohort. Accelerometry was used to measure physical activity (PA) and sedentary time over 4 days. Regression models were adjusted for clinical risk factor covariates. Results: Men were more sedentary than women ( P < 0.05), and sedentary time was negatively associated with spine BMD in men, with 84 minutes more sedentary time corresponding to 0.268 g.cm −2 lower BMD ( β = −0.268; P = 0.017). In men, light PA and steps/day were positively associated with bone geometry and BMD. Steps/day was positively associated with bone geometry and femur BMD in women, with a positive difference of 1415 steps/day corresponding to 0.232 g.cm −2 greater BMD ( β = 0.232, P = 0.015). Conclusions: Sedentary time was unfavourably associated with bone strength in men born in North East England at age 62 years. Higher volumes of light PA, and meeting the public health daily step recommendations (10 000 steps/day) was positively associated with bone health in both sexes.